Извори на правото во Византиската империја (компаративна анализа на државно-правниот систем) - Василевска, Иванка (Институт за национална историја, 2021)
Strictly centralized state and legal apparatus characterized the Byzantine Empire. The character of the arrangement was undoubtedly autocratic because the legislature, the executive and the judiciary were concentrated in the hands of the emperor. The diarchy introduced by Emperor Augustus for the joint rule of the ruler and the senate did not succeed in practice for a long time, and from the entry into power of Emperor Diocletian until the fall of the Empire, with few exceptions, was directly concentrated in the hands of the m1er. In that sense, the peculiarity of the Empire is the meaning of law. Although it came directly from the emperor and was a metaphorical source of the Byzantine law, legal norms and codifications were extremely important and they were a kind of brake or more precisely a compass in autocratic rule. Although is defined in science that the term Byzantine law itself did not represent the same legal order, and especially in the period from the sixth to the ninth century, the foundation on which it was built is found in the Roman legal foundations. It is important to emphasize that with the development of state-legal relations in Byzantine society, because of the changes in the Empire, the law gained medieval contours, although certain branches of law retained the principles that were structured in the time of Justinian. Despite all the changes, it is evident that the thesis of the sovereignty of law remained a lasting principle throughout the reign of the Byzantine Empire. Therefore, the aim of this paper is to present the sources of Law in the Empire and their developmental stages. In the form of a comparative analysis in which will be presented different types of legal acts, such as the Ekloga, the Law of Judgment of the People, the Agricultural Law (Nomos Georgikos), the Nomocanon of John the Scholastic and the Nomocanon of 14 titles.
Keywords: Византиска империја, правни извори.